2024
DOI: 10.1007/s00338-023-02454-9
|View full text |Cite
|
Sign up to set email alerts
|

How does warmer sea water change the sensitivity of a Mediterranean thermophilic coral after immune-stimulation?

L. Bisanti,
C. La Corte,
M. Dara
et al.

Abstract: Anthropogenic climate change is warming sea water worldwide, pushing the limits of tolerance for marine organisms and driving a decline in biodiversity. The risk of thermal anomalies has increased particularly in the Mediterranean region over the last 30 yrs, where intense warming has been identified as one of the main stressors in coastal regions. To determine the influence of warmer conditions on the immunity of an endemic Mediterranean coral species, different immune activity parameters were compared in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…This result is in agreement with documented increases in disease and disease-related mortality following coral bleaching in the wild. 24,40,44,96 Notably, while previous laboratory experiments have documented impacts of simultaneous heat stress and pathogen exposure 45,47,50,51,97 ours is the first to document the prolonged consequences of heat stress on pathogen susceptibility, more accurately representing observed environmental patterns in nature. Future studies combining our approach with emergent experimental disease techniques 98,99 will allow for more broadscale applications to complex cnidarian and marine disease systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in agreement with documented increases in disease and disease-related mortality following coral bleaching in the wild. 24,40,44,96 Notably, while previous laboratory experiments have documented impacts of simultaneous heat stress and pathogen exposure 45,47,50,51,97 ours is the first to document the prolonged consequences of heat stress on pathogen susceptibility, more accurately representing observed environmental patterns in nature. Future studies combining our approach with emergent experimental disease techniques 98,99 will allow for more broadscale applications to complex cnidarian and marine disease systems.…”
Section: Discussionmentioning
confidence: 99%
“…24,44 Despite these observations, nearly all experimental studies have focused on the synergistic effects of simultaneous heat stress and disease, specifically documenting increases in disease susceptibility when these stressors occur at the same time. 45,46 Synchronous associations between heat stress and increased pathogen susceptibility may be linked to heat induced suppression of immunity, [47][48][49][50][51] though other studies have instead demonstrated minimal or positive effects of heat stress on coral immunity. [52][53][54] Furthermore, it is unclear if similar mechanisms underly sequential associations between heat stress and disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%